LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN, PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN PENDEKATAN KAUSALITAS - Muhammad Rivandi; Sri Madona Saleh; Renil Septiano (JURNAL PUNDI, 2017)
Management of natural resources and environment who is not responsible the main issues disclosure of corporate social responsibility (Wahba & Elsayed, 2015). This study aims to examine the effect of leverage, profitability, and size toward the disclosure of corporate social responsibility. The samples of this study are 51 companies listed in Indonesia Stock Exchange selected by using purposive sampling method. Data analysis method used is panel regression model. The result this study tested that leverage has t statistics the biggest than t table (3,571 ≥  1,969), profitability has t statistic the biggest than t table (-2,495 ≥ - 1,969), and size of the firm has t statistic the biggest than t table (-1,961 ≥ -1,651). Base on hypothesis tested that the leverage, profitability, and size of the firm  have a significant effect toward disclosure of corporate social responsibility